Yahoo Web Search

  1. Sort by

  1. m= (x+y+z)/3 ...given m = x/3 + y/3 + z/3 ....distribute m = x/3 + z/3 + y/3 + -(y/3) ...subtract "y/3" from right side of the problem... m - y/3 = x/3 + z/3 ...where we should now be at -(m) + m - y/3 = x/3 + z/3 + -(m) ....subtract "m...

    2 Answers · Science & Mathematics · 22/10/2007

  2. M = xe^(y - z^4) partially differentiating with respect to x dM/dx = e^( y - z^4 ) dM / dy = x e^ ( y - z^4 ) dm / dz = - 4 x z^3 e^ ( y - z^4 ) dx / du = d ( 8 u v ) / d x = 8 v dx / dv = 8u lly dy / du = 1 and dy/dv...

    1 Answers · Science & Mathematics · 21/02/2010

  3. m = ∫∫∫ δ(x,y,z) dV ....= ∫(x = 0 to 2) ∫(y = 0 to...to 2) ∫(y = 0 to 2-x) ∫(z = 0 to 2-x-y) z^2 dz dy dx ....= 8/15 Hence, the center of mass (Mx/m, My/m, Mz/m) equals...

    1 Answers · Science & Mathematics · 05/05/2019

  4. x = y - m(y - z) x - y = -m(y - z) {subtracted y from both sides} -x + y = m(y - z) {divided both sides by -1} -x + y --------- = m {divided both sides by y - z} y - z http://www.algebrahouse.com

    2 Answers · Science & Mathematics · 21/10/2011

  5. ∇ = ( d/dx, d/dy, d/dz ) F = ( M(x, y, z), N(x, y, z), P(x, y, z) ) ∇•F = ( d/dx, d/dy, d/dz...

    1 Answers · Science & Mathematics · 29/06/2015

  6. X(m+5)+y(m-5)=z(m-4) Expand: mX + 5X + my - 5y = mz - 4z Gather... + my - mz = 5y - 5X - 4z Factor out m on the left: m (X + y - z) = 5y - 5X - 4z Divide by the non-m factor: m = ( 5y - 5X - 4z...

    1 Answers · Science & Mathematics · 29/01/2011

  7. m = ∫∫∫ ρ(x,y,z) dV ....= ∫(z = 1 to 5) ∫(y = 0 to 2) ∫(x = 1 to 3...dy * ∫(x = 1 to 3) x² dx ....= (1/2)z² {for z = 1 to 5} * (1/2)y² {for y = 0 to 2} * (1/3)x³ {for x = 1 to 3} ....= 12 * 2 * (26...

    1 Answers · Science & Mathematics · 04/03/2013

  8. Min is at x = y = 1 - √2 and z = -1 (M = 5 - 4√2) Max is at x = y = 1, z = 0, (M = 2) also at x = -1, y = -1, z= 0, (M =2)

    1 Answers · Science & Mathematics · 17/10/2008

  9. you just click on the letters Z-U-M-Y-L-O-V-E-J-I-N-G and then nancy will ask for that piece of paper

    2 Answers · Games & Recreation · 03/08/2006

  10. m = ∫∫∫s δ(x,y,z) dV = ∫∫∫s [10z^4 + 6(x^2 - y^2)^2] dV = ∫(θ = 0 to 2π... Simplifying, we get ∫(θ = 0 to 2π) ∫(r = 0 to a) ∫(z = 0 to h) [10z^4 + 6(r^2 cos(2θ))^2] * r dz dr dθ = ∫(θ = 0 to 2π) ∫(r...

    1 Answers · Science & Mathematics · 06/02/2011

  1. Try asking your question on Yahoo Answers